2019
DOI: 10.3390/ijms20143482
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Tolerance against a Fungal Pathogen and Insect Resistance in Transgenic Tobacco Plants Overexpressing an Endochitinase Gene from Serratia marcescens

Abstract: In this study we cloned a chitinase gene (SmchiC), from Serratia marcescens isolated from the corpse of a Diatraea magnifactella lepidopteran, which is an important sugarcane pest. The chitinase gene SmchiC amplified from the S. marcescens genome was cloned into the transformation vector p2X35SChiC and used to transform tobacco (Nicotiana tabacum L. cv Petit Havana SR1). The resistance of these transgenic plants to the necrotrophic fungus Botrytis cinerea and to the pest Spodoptera frugiperda was evaluated: bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 56 publications
1
10
0
Order By: Relevance
“…This confirmed that CpCHI4 could be a potent candidate gene to tackle H. armigera damage on crops corroborating with the demonstration of utilization of chitinase genes from various sources to control lepidopteron pests 13,48 . Furthermore, such genes of biochemical relevance to both insects as well as plants can be useful for resistance management, which otherwise has been a concern.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…This confirmed that CpCHI4 could be a potent candidate gene to tackle H. armigera damage on crops corroborating with the demonstration of utilization of chitinase genes from various sources to control lepidopteron pests 13,48 . Furthermore, such genes of biochemical relevance to both insects as well as plants can be useful for resistance management, which otherwise has been a concern.…”
Section: Resultssupporting
confidence: 72%
“…Alternatively, genes encoding for proteins with different defense functions such as digestive enzyme inhibitors 10 and proteins disrupting physical structures 11–13 in insect larvae have been successfully utilized for the development of insect resistance in plants. Among them, chitinase genes encoding enzymes that hydrolyze glycoside bonds in the chitin polymer have been well‐documented for insecticidal activity 13 . Chitin is known to be an important structural component of insect periplasmic membrane (PM) and is responsible for curtailing the entry of toxic chemicals, bacteria and viruses that infect insect cells 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Hence, biological control strategies tend to provide a plant protection solution that is environmentally friendly, ecologically viable and has great potential to promote sustainable agriculture. Microorganisms in the genera Bacillus, Pseudomonas, Serratia and fungi which belong to the genera Trichoderma are the common biocontrol agents used in the disease control of fungal pathogens [30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Due to these inherent chemical and physical characteristics of chitin its commercial applications in the native form are currently rather limited. Commonly native chitin is utilised as fertilizer in agriculture, as it contains nitrogen, or as an inducer of plant defence mechanisms, enhancing the resistance against fungi by the promotion of chitinases [21][22][23]. Furthermore, chitin is employed as a food additive [24] as well as a packaging material for affinity chromatography columns to purify proteins with a carbohydrate-binding domain, or as sorbent to pre-concentrate phenol and chlorophenols by means of solid phase extraction, as validated by HPLC [25,26].…”
Section: Chitinmentioning
confidence: 99%